National Health Interview Survey, 2003 ([Verlag nicht ermittelbar], 2005)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. Implementation of a redesigned NHIS, consisting of a basic module, a periodic module, and a topical module, began in 1997 (see NATIONAL HEALTH INTERVIEW SURVEY, 1997 [ICPSR 2954]). The 2003 NHIS contains the Household, Family, Person, Sample Adult, Sample Child, Child Immunization, and Injury and Poison Episode data files from the basic module. Each record in the Household-Level File (Part 1) contains data on type of living quarters, number of families in the household responding and not responding, and the month and year of the interview for each sampling unit. The Family-Level File (Part 2) is made up of reconstructed variables from the person-level data of the basic module and includes information on sex, age, race, marital status, Hispanic origin, education, veteran status, family income, family size, major activities, health status, activity limits, and employment status, along with industry and occupation. As part of the basic module, the Person-Level File (Part 3) provides information on all family members with respect to health status, limitation of daily activities, cognitive impairment, and health conditions. Also included are data on years at current residence, region variables, height, weight, bed days, doctor visits, hospital stays, and health care access and utilization. A randomly-selected adult in each family was interviewed for the Sample Adult File (Part 4) regarding respiratory conditions, renal conditions, AIDS, joint symptoms, health status, limitation of daily activities, and behaviors such as smoking, alcohol consumption, and physical activity. Also included in this file are variables pertaining to the Healthy People 2010 Objectives. The Sample Child File (Part 5) provides information from an adult in the household on medical conditions of one child in the household, such as respiratory problems, seizures, allergies, and use of special equipment like hearing aids, braces, or wheelchairs. Also included are variables regarding child behavior, the use of mental health services, and Attention Deficit Hyperactivity Disorder (ADHD). The Child Immunization File (Part 6) presents information from shot records on vaccination status, number and dates of shots, and information about the chicken pox vaccine. Episode-based information regarding injuries and poisonings is found in the Injury and Poison Episode File (Part 7), which examines the cause and date of injury or poisoning, loss of time from work or school, and whether the episode resulted in hospitalization. Information in the Injury and Poison Verbatim File (Part 8) is comprised of narrative text describing injuries, including type of injury, how the injury occurred, and the body part injured.